(untitled) (Economic and Political Thought, 2015)
The birth of the European Union took place in the period of peak impact of neoliberal trends on the global economy. The mechanisms of the EU are full of neoliberal ideas. This will prevent, over time, the implementation of the idea of social Europe formulated mainly by the European social democratic parties and nation states led by them. The mechanisms of neoliberal globalisation will dominate the processes of European integration.